Meeting the Sustainable Development Goal for Electricity Access : Using a Multi-Scenario Approach to Understand the Cost Drivers of Power Infrastructure in Sub-Saharan Africa - Nicolas, Claire; Samson, Benjamin; Rozenberg, Julie (World Bank, Washington, DC, 2019)
This paper explores the investments needed to achieve universal access to electricity in Sub-Saharan Africa by 2030, and the additional operation and maintenance costs these investments entail. It also explores the drivers of these costs, by exploring hundreds of scenarios that combine alternative assumptions on the level of service targeted, population growth, urbanization, industrial demand, and technology cost. The main driver of electrification costs is found to be the tier of service offered to newly connected households. The annual investment required to reach universal access varies between US$14.5 billion per year on average for the basic access scenarios (0.7 percent of the region's gross domestic product per year over the period) and US$22.7 billion on average for the high-quality scenarios (1 percent of gross domestic product). In the basic access scenario, costs depend mostly on industrial demand, which takes a large share of total demand. In the high-quality scenarios, costs depend on urbanization rates, as it is cheaper to connect urban households to the grid. Investment costs are not sufficient to provide reliable service, and when operations and maintenance are accounted for, total costs increase to US$39.7 billion on average for the basic scenarios and US$61.5 billion on average for the high-quality scenarios.